Antimicrobial efficacy of photosensitizers - Dr. Kanchana Sukumar,; Dr. Anupama Tadepalli,; Dr. Harinath.P,; Dr. Deepa.P, (International Journal of Pharma and Bio Sciences, 2020)
Inactivation of microorganisms using photodynamic therapy (PDT) has been defined as either antimicrobial photodynamic therapy (aPDT), Photodynamic antimicrobial chemotherapy (PACT) or photodynamic disinfection. Photodynamic therapy is a combination of nontoxic photosensitizer irradiated using visible light of appropriate wavelength, which in the presence of oxygen produces Reactive Oxygen Species (ROS). ROS is highly reactive and induces irreversible cytotoxic damage to the bacterial cell leading to the death of microorganisms. This review focuses on the various generations of photosensitizers and their antimicrobial effect against periodontal pathogens when used in periodontal and peri-implant disease management.